Antifibrotic, Antioxidant, and Immunomodulatory Effects of Mesenchymal Stem Cells in HOCl‐Induced Systemic Sclerosis. Issue 4 (April 2016) - Maria, Alexandre T. J.; Toupet, Karine; Bony, Claire; Pirot, Nelly; Vozenin, Marie‐Catherine; Petit, Benoît; Roger, Pascal; Batteux, Frédéric; Le Quellec, Alain; Jorgensen, Christian; Noël, Danièle; Guilpain, Philippe
Abstract : Objective: Systemic sclerosis (SSc) is a rare intractable disease with unmet medical need and fibrosis‐related mortality. Absence of efficient treatments has prompted the development of novel therapeutic strategies, among which mesenchymal stem cells/stromal cells (MSCs) or progenitor stromal cells appear to be one of the most attractive options. The purpose of this study was to use the murine model of hypochlorite‐induced SSc to investigate the systemic effects of MSCs on the main features of the diffuse form of the disease: skin and lung fibrosis, autoimmunity, and oxidative status. Methods: We compared the effects of different doses of MSCs (2.5 × 10 5, 5 × 10 5, and 10 6 ) infused at different time points. Skin thickness was assessed during the experiment. At the time of euthanasia, biologic parameters were quantified in blood and tissues (by enzyme‐linked immunosorbent assay, quantitative reverse transcription–polymerase chain reaction, assessment of collagen content). Assessments of histology and immunostaining were also performed. Results: A lower expression of markers of fibrosis ( Col1, Col3, Tgfb1, and aSma ) was observed in both skin and lung following MSC infusion, which was consistent with histologic improvement and was inversely proportional to the injected dose. Importantly, sera from treated mice exhibited lower levels of anti–Scl‐70 autoantibodies and enhanced antioxidant capacity, confirming the systemic effect of MSCs. Of interest, MSC administration was efficient in both the preventive and the curative approach. We further provide evidence that MSCs exerted an antifibrotic role by normalizing extracellular matrix remodeling parameters as well as reducing proinflammatory cytokine levels and increasing antioxidant defenses. Conclusion: The results of this study demonstrate the beneficial and systemic effects of MSC administration in the HOCl murine model of diffuse SSc, which is a promising finding from a clinical perspective.